Teacher Victimization: Understanding Prevalence, Causation, and Negative Consequences in a Large Metropolitan Area in the Southwestern United States, 2016-2017 - Moon, Byongook ([Verlag nicht ermittelbar], 2020)
This two-year longitudinal research examined the prevalence of seven different types of teacher victimization, its negative consequences among victimized teachers, and predictors of aggression directed against teachers. The research, using a stratified multistage cluster sampling design, surveyed 1,628 middle and high school teachers in 14 school districts, located in a large metropolitan area in the southwest region of the United States. Two waves of the longitudinal research collected 1) teachers' socio-demographic factors, 2) teacher classroom management styles, and 3) school climate factors which are related to teacher victimization. Also, the data contained characteristics of victimization, school responses to teacher victimization, and negative consequences of teacher victimization.